Effect of immersive virtual reality on pain in different dental procedures in children: a randomized controlled clinical trial - Alshatrat, Sabha Mahmoud; Sabarini, Jumana M.; Hammouri, Hanan M.; Alsaleh, Majd M.; Al-Bakri, Isra Abdulkarim; Tabnjh, Abedelmalek Kalefh (Frontiers in Oral Health, 2025)
IntroductionEffective pain management techniques are fundamental for enhancing patients' adherence to various pediatric dental procedures.ObjectiveThis study aims to evaluate the effectiveness of virtual reality (VR) on pain perception during dental procedures in children.MethodologyChildren aged between 5 and 12 years were recruited from a pediatric dental clinic. Ethical approval and informed consent were obtained from all parents or guardians. The need for different dental procedures was determined for each child based on the outcome of a clinical examination. Some of these procedures require local anesthesia (LA) administration, while others do not. The children were randomly assigned to either a VR or a non-VR group. Three behavioral scales, the Visual Analogue Scale (VAS), the Wong-Baker FACES Pain Rating Scale, and the “Face, Legs, Activity, Cry, and Consolability” (FLACC) Scale, were used to assess the pain level during dental procedures.ResultsA total of 154 children were recruited and evenly divided into VR and non-VR groups (77 each). The results of the study indicated that utilizing VR during dental procedures resulted in a significant reduction in pain perception (p < 0.05) and doubled the level of relaxation experienced by patients (70.31%), irrespective of anesthesia requirements. Statistical analysis revealed a significant difference between the VR and anesthesia groups across all VAS and Wong-Baker FACES variables.ConclusionThis research has confirmed that using virtual reality (VR) as a distraction technique effectively reduces pain during dental procedures for children. VR is a safe, non-invasive, and user-friendly technique that has gained interest as a non-pharmacological option for pain management. As a result, this promising approach has the potential to be used in clinical practice and should be further researched.